Retail wet markets, food handlers, and hospitalised patients as nodes in a shared non-typhoidal Salmonella ecosystem: a one health molecular epidemiological pilot study in Wuhan, China - Feng Tang; Zhi Chen; Shiyong Deng; Xiaomei Wang; Xuyang Gong; Ran Li; Lei Xi; Changzhen Li; Baoxiang Wang; Wanjun Luo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Multiband bipolar photoresponse in Cu@CuOx@a-Ga2O3 core-shell heterostructure-based self-powered photoelectrochemical-type photodetector for secure underwater optical communication - Yixin Sun; Yan Tang; Xiuhong Jiang; Aijiang Yan; Jin Zhao; Yuchuan Wang; Jiangshuai Luo; Jili Jiang; Ke Ding; Hong Zhang; Honglin Li; Di Pang; et al. (Chemical Engineering Journal, 2025)

No toxic effects or interactions between aflatoxin B1 and zearalenone in broiler chickens fed diets at China's regulatory limits - Wanjun Zhang; Yongpeng Jin; Ying Liu; Ruiqi Tan; Gaoyi Liu; Wenjun He; Sunlin Luo; Yutong Tang; Qiao Chen; Yiqiang Chen (Regulatory Toxicology and Pharmacology, 2025)

Toxicological risk assessment of triadimenol for human exposure, broiler health, and food safety - Yutong Tang; Ying Liu; Yongpeng Jin; Fude Zhang; Wanjun Zhang; Sunlin Luo; Jianjun Zang; Wenjun Yang; Yiqiang Chen (Food and Chemical Toxicology, 2024)

A Novel Platinum Resistance-Related Immune Gene Signature for Overall Survival Prediction in Patients with Ovarian Cancer - Chenfei Zhou; Junnan Ma; Wanjun Luo; Jiemei Hu; Jing Chen; Suiying Liang; Shanyang He (Biochemical Genetics, 2024)
Ovarian cancer (OV) is a highly heterogeneous gynecological tumor that makes the prognostic prediction challenging. Resistance to platinum-based chemotherapy is associated with a poor prognosis in OV. There seems to be an overlap between molecular mechanisms responsible for platinum resistance and immunogenicity in OV. However, the predictive role of platinum resistance-related immune genes for OV prognosis needs to be further explored. In our study, the mRNA expression data of OV patients with corresponding clinical information were collected from The Cancer Genome Atlas (TCGA) cohort and International Cancer Genome Consortium (ICGC) cohort. A multigene signature was constructed for OV patients in the TCGA cohort using the least absolute shrinkage and selection operator (LASSO) Cox regression model according to the optimal value of λ and was validated in the ICGC cohort. Furthermore, we performed functional analysis to explore the immune status between low- and high-risk groups based on the median value of the risk score for the multigene signature. Our data showed that there were 41.1% of the platinum resistance-related genes which differentially expressed between immune score low- and high-OV patients in the TCGA cohort. Univariate Cox regression analysis identified 30 differentially expressed genes (DEGs) associated with overall survival (OS) ( P P

Low-temperature CO selective catalytic reduction denitrification and sulfuric acid regeneration mechanism of Cu-Ce/AC catalyst poisoned with zinc salt - Zhenjing Wen; Bangfu Huang; Zhe Shi; Wanjun Li; Liubin Luo; Gaoyong Zi; Linjing Yang (Fuel, 2024)

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

Efficient hydrogen production in single-chamber microbial electrolysis cell with a fermentable substrate under hyperalkaline conditions - Wanjun Cui; Haiping Luo; Guangli Liu (Waste Management, 2023)

Benzotriazole-based structure in porous organic polymer enhancing O2 activation for high-efficient degradation of tetracycline under visible light - Yuancheng Qin; Zhenhua Jiang; Yue Guo; Muhammad Asim Mushtaq; Zhen Shen; Wanjun Du; Cailing Ni; Geng Luo; Yu Ji; Zhiqi Zhang; Yonggui Deng; Arshad Hussain; et al. (Chemical Engineering Journal, 2023)

Characterization of two novel Alu element-mediated α-globin gene cluster deletions causing α0-thalassemia by targeted next-generation sequencing - Zhiming Li; Xuan Shang; Shiqiang Luo; Fei Zhu; Xiaofeng Wei; Wanjun Zhou; Yuhua Ye; Tizhen Yan; Ren Cai; Xiangmin Xu (Molecular Genetics and Genomics, 2020)

Comparative Study of Metal Accumulation in Three Fish Species (Silurus asotus, Cyprinus carpio, and Carassius auratus auratus) from the Jinsha and Tuo Rivers Located Upstream of the Yangtze River, China - Jian Li; Yulian Yan; Nannan Yue; Qiyong Luo; Wanjun Li; Xiaojun Xie (Bulletin of Environmental Contamination and Toxicology, 2018)

MicroRNA-148a suppresses epithelial-to-mesenchymal transition by targeting ROCK1 in non-small cell lung cancer cells - Jipeng Li; Yulan Song; Yiping Wang; Jianping Luo; Wanjun Yu (Molecular and Cellular Biochemistry, 2013)